2015
DOI: 10.1088/2043-6262/6/2/025012
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of the vulcan XC-72R-supported Pt nanoparticles for the hydrogen evolution reaction in PEM water electrolysers

Abstract: Pt nanoparticles on vulcan XC-72R support (Pt/vulcan XC-72R) were prepared by the impregnation–reduction method. The Pt content, the morphological properties and the electrochemical catalysis of the Pt/vulcan XC 72R materials have been investigated by ICP-OES analysis, FESEM, TEM, and cyclic voltammetry. These materials were then used as catalyst for hydrogen evolution reaction at the cathode of proton exchange membrane (PEM) water electrolysers. The best catalyst was Pt/vulcan XC-72R prepared by the impregnat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 11 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…Hydrogen adsorption and desorption peaks were observed for Pt/KB in the potential range of 0.05-0.30 V for the reverse and forward scans, respectively. The electrochemical active surface area (ECSA) can be evaluated by integrating the area under the hydrogen adsorption or desorption peak, which was considered as an indicator of the number of catalytic Pt sites on the catalysts [19,20,23]. We found that the higher loading of Pt nanoparticles on KB, the larger the area under the hydrogen adsorption or desorption peaks.…”
Section: Sbet (M 2 G −1 )mentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen adsorption and desorption peaks were observed for Pt/KB in the potential range of 0.05-0.30 V for the reverse and forward scans, respectively. The electrochemical active surface area (ECSA) can be evaluated by integrating the area under the hydrogen adsorption or desorption peak, which was considered as an indicator of the number of catalytic Pt sites on the catalysts [19,20,23]. We found that the higher loading of Pt nanoparticles on KB, the larger the area under the hydrogen adsorption or desorption peaks.…”
Section: Sbet (M 2 G −1 )mentioning
confidence: 99%
“…Among active catalyst materials, platinum (Pt) is the most efficient catalyst for both HER and ORR [19][20][21][22]. In practical use, Pt nanoparticles (2-5 nm) are loaded onto various kinds of material supports (e.g., carbon black [23], carbon nanotubes [24], graphene [25], or metal oxide [26]) for use as HER/ORR catalysts. The most common method for synthesizing Pt nanoparticles relies on the bottom-up chemical reduction in water-soluble Pt 2+ or Pt 4+ ions as precursors (e.g., H 2 PtCl 6 , K 2 PtCl 4 , PtCl4, and Pt(AcAc) 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…Pt-catalysts for proton exchanged membrane fuel cells (PEMFCs) are carbon black (Vulcan XC-72) implanted with Pt nanoparticles (Pt/C) [ 1 , 2 ]. The carbon black (CB) subtracts function for both the conducting medium for the transportation of electrons from either cathode or anode, and O 2 trappers with suitable sizes of pores.…”
Section: Introductionmentioning
confidence: 99%
“…These Pt catalysts are usually supported on high-surface carbon and/or nano-carbon such as Vulcan XC-72, and so on. [5][6][7][8] The support carbon materials are manufactured from the hydrocarbons such as natural gas or oil fractions by the pyrolysis process. These support carbon materials are commonly used for the PEMFC at present.…”
Section: Introductionmentioning
confidence: 99%